ANALISIS SAMPAH ORGANIK SEBAGAI “ECO GARBAGE ENZYME” UNTUK PERTUMBUHAN TANAMAN SELADA (Lactuca Sativa L.) - Yuliandewi, Ni Wayan; Sukerta, Made; Wiswasta, IGN Alit; Wahyuni, Febria (Jurnal Alam Lestari, 2021)
From the observation results conducted in the Badung market, organic waste deposits have the highest percentage, reaching 71.51%. The alternative of the market waste processing, especially vegetable and fruit skin organic waste, is by making environmentally friendly biopesticides. This biopesticide is called an eco garbage enzyme. This eco garbage enzyme is applied as an environmentally friendly biopesticide that will be used in hydroponic lettuce plants so that it can realize a healthy life style. This research aims to study the processing of organic waste into eco garbage enzyme of waste, and increase the effect of eco garbage enzyme on lettuce plants and increase the influence of eco garbage enzyme as environmentally friendly pesticides on lettuce plants. This study included experimental research with quantitative descriptive methods. This study produced an eco garbage enzyme which is the result of semi-aerobic fermentation that can be applied as an environmentally friendly biopesticide. This eco garbage enzyme make a significant contribution to root length, stem circumference, and dry weight of lettuce plants with the best concentration, namely 10 cc / L. environmentally friendly waste enzyme concentration